The Effectiveness of Mediation as an Alternative to Medical Dispute Resolution: A Systematic Review - Wiwin Yuli Triana; Sulistyorini Sulistyorini (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Expectations for health services provided by health workers are not always following the expectations of patients and families. This gap often leads to dissatisfaction, leading to health disputes. Dispute resolution can be done through litigation or non-litigation, one of which is through non-litigation which can be used is mediation. A Systematic review is in line with PRISMA guidelines. Four databases were systematically searched (PubMed, Science Direct, Proquest, Springerlink). For quantitative studies describing the effectiveness of mediation using predefined search strategy and any relevant keywords. A total of 10 out of 338 studies were included. Only medical dispute resolution mediation included and only for health worker. The study design used includes a literature review, cross-sectional study, and qualitative study. The average number of participants was more than one thousand overall for every study. Mediation as an alternative dispute resolution provides a solution to open communication between disputing parties.